Integration of Information Technology Systems in English Learning Management - Sembiring, Friscilla; Sitepu, Conie Nopinda Br (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the integration of technology in English language learning among junior high school students. By utilizing various digital technologies, the study highlights the significant benefits of using technology, in terms of English language learning materials and better collaboration. However, the study also identifies challenges faced, such as the digital divide, lack of teacher training, and the need to balance digital interactions with face-to-face learning. Key findings suggest that while technology can significantly assist in English language learning, a comprehensive approach is needed to address these challenges and create an effective educational environment. The study provides insights into the importance of digital literacy, ongoing teacher training, and the need for technology integration in English language teaching.